2022
DOI: 10.1155/2022/2501279
|View full text |Cite
|
Sign up to set email alerts
|

Focus on the Mechanisms and Functions of Pyroptosis, Inflammasomes, and Inflammatory Caspases in Infectious Diseases

Abstract: Eukaryotic cells can initiate several distinct self-destruction mechanisms to display essential roles for the homeostasis maintenance, development, and survival of an organism. Pyroptosis, a key response mode in innate immunity, also referred to as caspase-1-dependent proinflammatory programmed necrotic cell death activated by human caspase-1/4/5, or mouse caspase-1/11, plays indispensable roles in response to cytoplasmic insults and immune defense against infectious diseases. These inflammatory caspases are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 221 publications
(253 reference statements)
0
8
0
Order By: Relevance
“…When germs, pathogens, or endotoxins stimulate cells, the caspase family becomes active, triggering pyroptosis, also known as inflammatory cell death. As a result of this process, cell swelling, cell membrane pore formation, cell membrane rupture, inflammasome activation, and finally the release of cell contents and inflammatory mediators all occur, culminating in severe inflammatory responses (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…When germs, pathogens, or endotoxins stimulate cells, the caspase family becomes active, triggering pyroptosis, also known as inflammatory cell death. As a result of this process, cell swelling, cell membrane pore formation, cell membrane rupture, inflammasome activation, and finally the release of cell contents and inflammatory mediators all occur, culminating in severe inflammatory responses (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Prostatitis is an inflammatory disease that is linked to both infectious and non-infectious factors. Pyroptosis has turned out to be present in a variety of infectious and sterile diseases (60)(61)(62)(63)(64). The pyroptotic cells are able to promote the development of an inflammatory response by secreting the necessary cellular components and inflammatory mediators.…”
Section: Prostatitismentioning
confidence: 99%
“…[56] ALI resulting from infectious factors, such as bacteria, fungi, and viruses, has been demonstrated to be associated with AM pyroptosis. [57,58] On the one hand, pyroptosis of AMs is beneficial for resisting the invasion of different pathogens, and on the other hand, the release of plentiful inflammatory cytokines and the imbalance in the inflammatory response both amplify the inflammatory response, leading to the deterioration of ALI. [59] Thus far, it has been demonstrated that the specific mechanisms behind the induction of pyroptosis in macrophages vary from pathogen to pathogen.…”
Section: Pyroptosis Of Lung Macrophagesmentioning
confidence: 99%
“…AMs are essential for maintaining the stability of lung homeostasis and resisting invasion from the extrapulmonary environment, while IMs have an irreplaceable function in homeostasis regulation [56] . ALI resulting from infectious factors, such as bacteria, fungi, and viruses, has been demonstrated to be associated with AM pyroptosis [57,58] . On the one hand, pyroptosis of AMs is beneficial for resisting the invasion of different pathogens, and on the other hand, the release of plentiful inflammatory cytokines and the imbalance in the inflammatory response both amplify the inflammatory response, leading to the deterioration of ALI [59] …”
Section: Pyroptosis In Acute Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation